IMPLEMENTASI PROGRAM PEMENUHAN HAK KESEJAHTERAAN SOSIAL MELALUI REHABILITASI SOSIAL BAGI PENYANDANG DISABILITAS FISIK DI KABUPATEN KARAWANG - Ananda Aprillia; Cucu Sugiarti; Lina Aryani (Institut Pemerintahan Dalam Negeri, 2021)
This research is motivated by the difficulty of people with disabilities, especially people with physical disabilities in Karawang Regency in obtaining social welfare in their lives, as evidence that the Karawang Regency Government still lacks attention to people with disabilities. The purpose of this study was to find out how the implementation of the program to fulfill social welfare rights through social rehabilitation for persons with physical disabilities in Karawang Regency. The research uses qualitative methods with the type of case study research. Data collection techniques in research are through observation, interviews, and documentation. The results showed that the implementation of the program to fulfill the rights of social welfare through social rehabilitation for persons with physical disabilities in Karawang Regency has been going well but cannot be said to be optimal. Because there are still some problems in the implementation of social rehabilitation programs that need to be improved again. So that the implementation of the program every year can run optimally so that people with physical disabilities in Karawang Regency are easily obtain social welfare in their lives.